Antioxidant activity of yeast derivatives: Evaluation of their application to enhance the oxidative stability of white wine. (15th December 2022) - Nioi, Claudia; Lisanti, Maria Tiziana; Meunier, Fabrice; Redon, Pascaline; Massot, Arnaud; Moine, Virginie
Abstract: Maintaining wine oxidative stability and reducing SO2 addition remains a challenge in white winemaking. This study aimed to evaluate the antioxidant capacity of two yeast derivatives (YDs) with a specific composition: one was rich in reducing compounds, including glutathione (YDR ), and the other was rich in lipid compounds (YDL ). Both YDs were evaluated for their antiradical activity in model wine solution (by the DPPH method) and for their capacity to consume oxygen in model wine solution and in white wine. Antiradical activity in both matrixes and oxygen consumption rate in wine were higher for YDL than for YDR . However, the addition of YDR to wine limited the production of acetaldehyde and preserved glutathione content to a greater extent after wine oxygenation. The sensory analysis confirmed that both YDs, in particular YDL, limited the occurrence of oxidation off-odours when no SO2 was added. These data suggest that the use of YDs could be effectively implemented in low-sulfite winemaking in order to improve the antioxidant protection of white wine. Highlights: The use of yeast derivatives (YDs) as antioxidants in white wine was evaluated. Antioxidant activity were evaluated by DPPH and Oxygen Consumption Rate method. The addition of YDs to white wine limited the production of acetaldehyde. The addition of YDs to white wine permitted to preserve wine glutathione content. YDs limited the color browning and oxidation off-odours in absence of SO2 addition.